Total knee replacement: 12 years retrospective review and experience - Zulkifly, Ahmad Hafiz; Omar, Masbah; Simanjuntak G, Ruslan (Malaysian Orthopaedic Association, 2011)
This retrospective study was undertaken to evaluate the outcome of primary total knee arthroplasty (TKA)performed from January 1986 to December 1997 at this institution. Case review included Knee Society scores and functional knee score. The records of 94 patients (128 knees) were available for analysis with the sample comprised of 76 females (80.9%) and 18 males (19.1%) and a mean age was 61.4 years. TKA was performed for osteoarthritis (OA) in 96 knees (75%) and rheumatoid arthritis (RA) in 32 knees (25%). Cemented TKAs were performed in all patients. The mean knee score improved from 38.8 preoperatively to 90.9 postoperatively. The mean functional score improved from 19.1 preoperatively to 62.5 postoperatively. Both scores showed significant improvement when comparing preoperative to post operative results (p< 0.005). Arthroplasty was designated failures if the prostheses used had been removed. Survivorship at 12 years was 89.5%.